Biology and Management of Glyphosate-Resistant and Glyphosate-Susceptible Palmer Amaranth (Amaranthus palmeri) Phenotypes from a Segregating Population. Issue 6 (24th August 2017) - Chaudhari, Sushila; Jordan, David L.; York, Alan C.; Jennings, Katherine M.; Cahoon, Charles W.; Chandi, Aman; Inman, Matthew D.
Abstract : Palmer amaranth is the most economically damaging glyphosate-resistant (GR) weed in the southern United States. An understanding of the basic biology, including relative growth and competitiveness of GR and glyphosate-susceptible (GS) Palmer amaranth phenotypes from a segregating population collected from the same geographical location, may yield information helpful in the management of resistant populations. A segregating population of Palmer amaranth collected in North Carolina during 2010 was used as a plant source for both GR and GS traits. Research was conducted in the greenhouse to compare the following: level of resistance and shikimate accumulation in GR and GS phenotypes following glyphosate application; interference from GR and GS phenotypes on early-season vegetative growth of corn, cotton, and peanut; effect of various durations of imposed drought stress on GR and GS phenotypes; and response of GR and GS phenotypes to POST-applied herbicides. The GR50 (glyphosate rate providing 50% reduction in shoot dry biomass) was 17 times greater with the GR phenotype compared with the GS phenotype. Shikimate accumulated in both GR and GS phenotypes following glyphosate application, but greater concentrations were found in GS plants. The GR and GS phenotypes responded similarly when subjected to drought stress; grown with corn, cotton, and peanut; or treated with 2, 4-D, atrazine, dicamba, fomesafen, glufosinate, paraquat, tembotrione, and thifensulfuron. These results indicate that in the absence of glyphosate selection pressure, resistance to glyphosate does not influence the growth and competitiveness of GR and GS Palmer amaranth phenotypes collected from the same geographical location.